2005
DOI: 10.1128/aem.71.10.6142-6149.2005
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Anammox Activity and Microscale Distribution of Nitrite in a Subtropical Mangrove Sediment

Abstract: The distribution of anaerobic ammonium oxidation (anammox) in nature has been addressed by only a few environmental studies, and our understanding of how anammox bacteria compete for substrates in natural environments is therefore limited. In this study, we measure the potential anammox rates in sediment from four locations in a subtropical tidal river system. Porewater profiles of NO x ؊ (NO 2 ؊ plus NO 3 ؊ ) and NO 2 ؊were measured with microscale biosensors, and the availability of NO 2 ؊ was compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
147
3
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(165 citation statements)
references
References 38 publications
13
147
3
2
Order By: Relevance
“…Meyer et al (2005) reported AN from a subtropical sediment, correlated with benthic nitrite distribution. Nicholls and Trimmer (2009) have argued that the importance of AN potential increases with both organic carbon content of sediment and with nitrate concentration in the overlying water, and that there is increase of AN relative to DN at lower temperature (Dalsgaard and Thamdrup 2002;Rysgaard et al 2004) .…”
Section: Discussionmentioning
confidence: 99%
“…Meyer et al (2005) reported AN from a subtropical sediment, correlated with benthic nitrite distribution. Nicholls and Trimmer (2009) have argued that the importance of AN potential increases with both organic carbon content of sediment and with nitrate concentration in the overlying water, and that there is increase of AN relative to DN at lower temperature (Dalsgaard and Thamdrup 2002;Rysgaard et al 2004) .…”
Section: Discussionmentioning
confidence: 99%
“…Our future effort will focus on the enrichment of the members of this cluster in a laboratory scale bioreactor. Anammox metabolism in marine ecosystems was an important discovery for the oceanic nitrogen cycle (Dalsgaard et al, 2003;Kuypers et al, 2003;Meyer et al, 2005); anammox bacteria highlighted in hydrothermal ecosystems could allow a better comprehension of the nitrogen cycle in the deep ocean.…”
Section: Activity Measurementsmentioning
confidence: 99%
“…The potential for anammox has now been reported for sediments from estuaries (Trimmer et al 2003;RisgaardPetersen et al 2004;Meyer et al 2005) and coastal seas Thamdrup and Dalsgaard 2002;Rysgaard et al 2004) and, in addition, several anoxic bodies of water Kuypers et al 2003Kuypers et al , 2005. The contribution of anammox to N 2 production has been found to be very high in some sediments, accounting for up to 80% of N removal (Engströ m et al 2005).…”
mentioning
confidence: 99%
“…The precise regulation of anammox in sediments is, as yet, unclear, though the current dogma is that denitrification decreases relative to anammox with increasing water depth offshore because of the associated decrease in availability of organic carbon needed to drive sediment mineralization and, thus, denitrification Dalsgaard et al 2005;Engströ m et al 2005). In addition, anammox may be favored in colder regions and-or those systems where NO { 3 and its reduction to NO { 2 are both high and consistent Meyer et al 2005;Trimmer et al 2005). Despite this progress the majority of studies on anammox and denitrification in sediment are potentials based on anaerobic slurry incubations.…”
mentioning
confidence: 99%